Mismatch between obesogenic intrauterine environment and low‐fat postnatal diet may confer offspring metabolic advantage - Sezen Kislal; William Jin; Claire Maesner; Andrea G. Edlow (Wiley, 2021)
Abstract Objective Mismatch between a depleted intrauterine environment and a substrate‐rich postnatal environment confers an increased risk of offspring obesity and metabolic syndrome. Maternal diet‐induced obesity (MATOB) is associated with the same outcomes. These experiments tested the hypothesis that a mismatch between a nutrient‐rich intrauterine environment and a low‐fat postnatal environment would ameliorate offspring metabolic morbidity. Methods C57BL6/J female mice were fed either a 60% high‐fat diet (HFD) or a 10% fat control diet (CD) for 14‐week pre‐breeding and during pregnancy/lactation. Offspring were weaned to CD. Weight was evaluated weekly; body composition was determined using EchoMRI. Serum fasting lipids and glucose and insulin tolerance tests were performed. Metabolic rate, locomotor, and sleep behavior were evaluated with indirect calorimetry. Results MATOB‐exposed/CD‐weaned offspring of both sexes had improved glucose tolerance and insulin sensitivity compared to controls. Males had improved fasting lipids. Females had significantly increased weight and body fat percentage in adulthood compared to sex‐matched controls. Females also had significantly increased sleep duration and reduced locomotor activity compared to males. Conclusions Reduced‐fat dietary switch following intrauterine and lactational exposure to MATOB was associated with improved glucose handling and lipid profiles in adult offspring, more pronounced in males. A mismatch between a high‐fat prenatal and low‐fat postnatal environment may confer a metabolic advantage. The amelioration of deleterious metabolic programming by strict offspring adherence to a low‐fat diet may have translational potential.